Pengaruh Eksistensi Bahasa Lampung Terhadap Pengembangan Pariwisata Di Kabupaten Lampung Barat - M. Ghibras Abigail (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
Current conditions in Indonesia, of the 617 identified regional languages, 15 regional languages ​​are declared extinct and 139 others are in endangered status. Information on the threat of extinction of regional languages ​​was stated by Dadang Sunendar as Head of the Language Development and Development Agency of the Ministry of Education and Culture through his research results, after attending the Nusantara Regional Language Congress at the Merdeka building, Bandung in 2016 (Permata and Abidin, 2020). This study aims to determine the effect of the existence of the Lampung language on tourism development in West Lampung Regency. The method used in collecting data in this study is descriptive. In this study, the descriptive method was used to identify and describe tourism development in West Lampung Regency. The data collection instrument used a literature study by collecting and studying several references through documents such as regulations, as well as book and journal references related to the Lampung language and tourism development in West Lampung Regency. Based on the results of this study, the introduction of the existence of the Lampung language can be a trigger for teenagers to use the Lampung language again in their daily lives and feel proud to introduce it to tourists in West Lampung Regency. In addition, the existence of the Lampung language can be used as an evaluation in areas that have similar problems and can introduce various cultures through local languages.